Correlation between Perfusion Index and Left Ventricular Output in Healthy Late Preterm Infants - Aytekin, Ayca; Hakan, Nilay; Ilhan, Ozkan; Aydin, Mustafa; Olgun, Hasim (Thieme Medical Publ Inc, 2023)
Aim The perfusion index (PI) is a noninvasive marker derived from photoelectric plethysmographic signals in pulse oximetry in the evaluation of peripheral perfusion. This study was aimed to determine the correlation between PI and left ventricular output (LVO) in healthy late preterm infants at 48 (th) hour of life. Methods With new generation pulse oximeter (MASIMO Rad 7 Oximeter) pre- and post-ductal PI values were recorded from healthy late preterm babies at the 48 (th) hour of life. PI was determined simultaneously with LVO as measured by transthoracic echocardiography. Results A total of 50 late preterm babies were included in the study. The mean gestational age of the cases was 35.4 +/- 0.7 weeks and the birth weight was 2,586 +/- 362 g. Mean pre- and post-ductal PI values at the postnatal 48 (th) hour of babies' life were found to be 2.0 +/- 0.9 and 1.7 +/- 1.1. The mean LVO value was 438 +/- 124, LVO/kg 175 +/- 50. When the LVO value was normalized according to the babies' body weight, there was no statistically significant correlation between the pre- and post-ductal PI and the LVO/kg value ( r <0.2, p >0.05 in both comparisons). Conclusion There was no correlation between pre- and post-ductal PI and LVO values in healthy late preterm infants. This may be due to the failure of the LVO, a systemic hemodynamic parameter, to accurately reflect microvascular blood flow due to incomplete maturation of the sympathetic nervous system involved in the regulation of peripheral tissue perfusion in preterm babies.
Keywords: perfusion index; left ventricular output; late preterm infants; echocardiography